UMPSA empowers Local Fish Ornamental - Wan Noor Farah, Wan Shamsuddin; Arulselvi, Uthayakumaran (UMPSA, 2024)
PEKAN, 20 December 2024- Centre for Modern Languages (CML), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has successfully conducted a Corporate Social Responsibilities (CSR) with the Port Dickson Ornamental Fish Centre to assist with the translations of the fish descriptions.